Certain Aspects of Mythical Meaning of Frog in the Traditional Lithuanian Worldview - Džekčioriūtė, Vita (Tautosakos darbai, 2014)
The article is based on the traditional Lithuanian beliefs and customs recorded in the end of the 19th – first half of the 20th century. It aims at proving that frog in Lithuanian culture has its own unique realm of mythical meanings, which only partly correspond to those of the toad’s. In this realm, several groups of meanings associated with frog can be discerned. Firstly, frog is considered to be an accumulator of water in the popular meteorology. Its enhanced activity, its enlarged body or darkened color may indicate the approach of the rain. People used to believe that killing of a frog resulted in downpour, since such an act symbolically released the atmospheric water that had been accumulated in its body. A second group of mythical meanings associated with frog present it as a creature endowed with healing powers. Here, its cold-bloodedness is most important. Illness or physical malfunction represent the hot pole of the opposition hot vs. cold, while frog represents the cold one, thus being able to neutralize the heat resulting from illness. In the third group, frog is regarded as a zoomorphic part of the human body or as a foreign body embedded in it. A creature in frog’s shape is believed to live in the human belly. As result of physical malfunction, it may move and leave its place, finding itself close to the heart or in the throat. Having lost this part of the body, the person dies. So whenever this frog-like creature, commonly also called macica (womb) or gumbas (lump) moves, it is attempted to restore it back to its former place. Frog, regarded as a foreign body, is believed also to sit on the human brain, thus causing psychic diseases. In such case, the person is treated by attempting to lure the frog out of the body. In the fourth group of mythical meanings, tight connections between frogs and children are displayed. Both frogs and children are related to water and humidity. This idea is reflected in the notion of people being born from a water body. Little children, just like frogs, are characterized by poorly coordinated movements and inarticulate sounds. The smaller the child, the closer it seems to the frog. This association is best reflected by calling little kids frogs in Lithuanian. From such folk identification of children and frogs there also stems the traditional explanation typically given to children by grown-ups, of the children being brought by the stork. In the fifth group of mythical meanings, frog is presented as a threatening aquatic creature, which is used to scare the kids away from water. Frog is therefore considered as possible prototype of all the other scary beings residing in water.
Keywords: -